Effect of ultrasonication and other processing conditions on the morphology, thermomechanical, and piezoelectric properties of poly(vinylidene difluoride‐trifluoroethylene) copolymer films. Issue 6 (10th July 2013) - Nguyen, Van Son; Rouxel, Didier; Meier, Matthias; Vincent, Brice; Dahoun, Abdesselam; Thomas, Sabu; Santos, Fabrice Domingues Dos
<x xml:space="preserve">Abstract</x> This study is carried out on the effect of processing conditions including preparation methods, ultrasonication, film thickness, and thermal annealing on the thermal, mechanical, and piezoelectric properties of copolymer of poly(vinylidene difluoride‐trifluoroethylene) (P(VDF‐TrFE)). Free‐standing films and films on substrates are prepared by solvent casting and spin‐coating, respectively. The results obtained by differential scanning calorimetry show that the Curie transition of the copolymer films was influenced by the preparation methods, with very little difference in the melting transition. The difference was attributed to a less uniform distribution of TrFE comonomer units within the crystalline and amorphous regions of the spin‐coating films. However, no effect of the preparation methods on the piezoelectric properties of the films was observed. It is also found that the short ultrasonication, film thickness higher than critical value of crystallization of P(VDF‐TrFE) (about 100 nm), and drying before annealing did not have a significant effect on the properties of the films. Surprisingly, the ultrasonication had a clear impact on the relaxations at high temperature of the polymer chains. In addition, this study indicates that a short annealing by 10 min at 140°C was enough to obtain well‐crystallized films, which is interesting from the industrial point of view. POLYM. ENG. SCI., 54:1280–1288, 2014. © 2013 Society of Plastics Engineers